The COMBI Approach in Managing Dengue Cases in an Urban Residential Area, Nilai, Malaysia. - Rozita Hod,; Hidayatulfathi Othman,; Nurul Azimah Jemain,; Mazrura Sahani,; Kamarulismail Udin,; Zainudin Mohd Ali,; Er, Ah Choy; Zailiza Suli, (Universiti Kebangsaan Malaysia, 2013)
Dengue is a disease propagated by vectors namely Aedes spp. mosquitoes.One of the effective approaches to control dengue is through integratedvector management and intervention programs. COMBI or Communicationfor Behavioral Impact is a strategic approach to control the Aedes population as well as dengue cases.